Special education for all teachers - Colarusso, Ronald P.; O'Rourke, Colleen M. ;Leontovich, Melissa A. (Dubuque : Kendall Hunt Publishing Company, 2013)
This textbook is for all professionals who are interested in the education of students with special needs. These students include not only those with disabilities, but also those who are culturally and linguistically diverse, and those who are at risk of academic failure for any reason. The intent of this book is to provide information and increase knowledge about these students in the hope that greater understanding will lead to the acceptance of them and their diverse needs in our schools and our society. This book is to serve as a text for students enrolled in preservice courses addressing at-risk learners. It also is intended to provide instructional and management strategies for general education classroom teachers who interact with these students on a daily basis. In addition, it can serve as a supplemental text or resource for those professionals currently serving students with special needs.
1. Teaching Every Student: A Mandate for Today -- 2. The Legal Foundation for Special Education -- 3. The Response to Intervention, Referral, and Placement Process -- 4. Collaboration with Families and Professionals -- 5. Cultural and Linguistic Diversity: Issues in Education -- 6. Students with Learning Differences Affecting Achievement -- 7. Approaches to Instruction for Students with Learning Differences -- 8. Students with Behavior Differences Affecting Achievement -- 9. Managing Behavior for Effective Learning -- 10. Students with Autism Spectrum Disorders -- 11. Students with Sensory, Communication, Physical, and Health Impairments -- 12. Students with Moderate to Severe Intellectual Disabilities -- 13. Gifted and Talented: The Overlooked Exceptionality.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION